(untitled) (Науковий журнал «Наукові записки Національного університету «Острозька академія»: серія «Філологія», 2020)
The proposed article deals with the Sorabistic works of professor of the Department of Slavic Philology named after Ilarion Sventsycki, literary critic Volodymyr Andriyovych Motornyi. Professor Volodymyr Motornyi, for his many years of scientific work, paid much attention to the study of the literature and culture of the Lusatian Serbs. He devoted more than fifty years to work at the Lviv National University and studying various Slavic literatures and cultures: Bulgarian, Serbian, Polish, Slovak. Most of the scientific works of the scientist are devoted to the history of Czech literature, its formation and development, but V. Motorny never forgot about the life of the smallest Slavic folk – Lusatian Serbs. Lusatian literature, its difficult history in the absence of statehood and with a constant alien environment, was a kind of hobby for him. V. Motorny was personally acquainted with several Lusatian writers, maintained contact with them, often visited them and invited them to Ukraine, and also popularized in every way the Lusatian literature in Ukraine. He wrote series of articles about Lusatian writers in leading encyclopedias of the former USSR and Ukraine. The article deals with the works of V. Motornyi, dedicated to the contacts of I. Franko with famous figures of the Lusatian culture, including the poet J. Bart-Ćiśinski. The article gives an overview of the most important scholar’s Sorabistic works; particular attention is paid to those works that in one way or another touch upon the issues of Lusatian-Ukrainian literary and cultural relations.